Potency of local feed ingredients and ability of livestock to use the feed: An in-vitro study - Nurina Rahmawati (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The study obtained data on the potential of local feed ingredients, both in quantity, quality, and continuity and to observe the absorption power and ability of livestock to use feed designed in vitro. Materials and Methods: The method uses a survey method of potential sources of animal feed and calculates the carrying capacity of ruminants and nutritional analysis of feed ingredients with proximate analysis. Feed formulations were made based on proximate analysis results of four formulas (P1, P2, P3, and P4) and tested in vitro. Results: First, Nganjuk district has the highest of the local food potential with the production of agricultural waste and agricultural industries, reaching 802,341.94 tons/year. Second, the most top carrying capacity analysis reached in Tulungagung district, which reached 62,534 ST/year or 43% of the total population of ruminants. Third, the results of the study of the quality of local feed ingredients indicate that each type of feed material has the right and proper nutrition given to ruminants. Fourth, the in vitro testing included showing P1 feed that had a very significant effect (p < 0.01) on dry matter digestibility and digestibility of organic matter of cows, respectively, 74.69% and 73.39%. Conclusion: The in vitro technique of making animal feed can be developed in the areas that have the potential to produce agricultural waste and agricultural industries to increase the carrying capacity of livestock. [J Adv Vet Anim Res 2020; 7(1.000): 92-102]